The spray-paint mystery - Medearis, Angela Shelf, 1956-; Williams, Richard, 1950-; Copyright Paperback Collection (Library of Congress) (New York, NY : Scholastic Inc., 1996)
Someone's been painting graffiti on the walls. It's up to Cameron to find out who and prove that he can be a great detective just like his dad. With help from his best friend, Tarann, it's up to him to solve this paint puzzle!
"A Little Apple paperback."
G2
Keywords: Detective and mystery stories; Graffiti -- Juvenile fiction; Mystery fiction; Children's stories